2022
DOI: 10.1007/s00429-022-02493-y
|View full text |Cite
|
Sign up to set email alerts
|

The role of the angular gyrus in semantic cognition: a synthesis of five functional neuroimaging studies

Abstract: Semantic knowledge is central to human cognition. The angular gyrus (AG) is widely considered a key brain region for semantic cognition. However, the role of the AG in semantic processing is controversial. Key controversies concern response polarity (activation vs. deactivation) and its relation to task difficulty, lateralization (left vs. right AG), and functional–anatomical subdivision (PGa vs. PGp subregions). Here, we combined the fMRI data of five studies on semantic processing (n = 172) and analyzed the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 93 publications
5
19
1
Order By: Relevance
“…In support of this view, Jung-Beeman (2005) summarized evidence that both the left and right hemispheres are engaged in conceptualsemantic cognition, but the right hemisphere seems to perform coarser computations than the left. This view is also corroborated by a recent large-scale fMRI study (n=172) which revealed conceptual effects in both the left and right IPL, but stronger in the left (Kuhnke, Chapman et al, 2022).…”
Section: These Findings Extend Previous Results From Univariate Neuro...supporting
confidence: 75%
See 1 more Smart Citation
“…In support of this view, Jung-Beeman (2005) summarized evidence that both the left and right hemispheres are engaged in conceptualsemantic cognition, but the right hemisphere seems to perform coarser computations than the left. This view is also corroborated by a recent large-scale fMRI study (n=172) which revealed conceptual effects in both the left and right IPL, but stronger in the left (Kuhnke, Chapman et al, 2022).…”
Section: These Findings Extend Previous Results From Univariate Neuro...supporting
confidence: 75%
“…Cross-modal convergence zones integrate modality-specific features into more abstract, cross-modal representations (Binder, 2016;Fernandino et al, 2016a;Kuhnke et al, 2023Kuhnke et al, , 2020bTong et al, 2022). We previously proposed a distinction among cross-modal convergence zones between "multimodal" regions which retain modality-specific information, and "amodal" regions which completely abstract away from modality-specific input (Kuhnke et al, 2023(Kuhnke et al, , 2022(Kuhnke et al, , 2020b. Multimodal regions seem to include the left inferior parietal lobe (IPL) and posterior middle temporal gyrus (pMTG) (Fernandino et al, 2022(Fernandino et al, , 2016aKuhnke et al, 2023Kuhnke et al, , 2020b, whereas the anterior temporal lobe (ATL) acts as an amodal hub of the conceptual system (Jefferies, 2013;Lambon Ralph et al, 2016;Patterson et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Third, control regions are expected to show stronger activation for harder tasks (Noonan et al, 2013). In contrast, a recent large-scale fMRI study (N = 172) revealed that multimodal IPL shows the opposite relationship: lower activity for harder tasks (Kuhnke et al, 2022). Moreover, left IPL was not engaged in a recent metaanalysis of "semantic control"-the controlled retrieval of conceptual information (Jackson, 2021).…”
Section: Multimodal Convergence Zones For Conceptual Processingmentioning
confidence: 93%
“…In contrast to the "amodal" ATL, "multimodal" hubs like left IPL and pMTG retain modality-specific perceptual-motor information about the individual modalities that they bind (Fernandino et al, 2016b;Kuhnke et al, 2022Kuhnke et al, , 2021Kuhnke et al, , 2020bReilly et al, 2016b;Seghier, 2013). Hence, these regions are sensitive to modality-specific conceptual information related to several modalities.…”
Section: Multimodal Vs Amodal Hubsmentioning
confidence: 99%
See 1 more Smart Citation